DNA barcoding coupled with high resolution melting for rapid identification of Ardisia gigantifolia and its toxic adulterants - Bo Zhao; Chao Xiong; Lan Wu; Li Xiang; Yuhua Shi; Wei Sun; Shilin Chen (Biotechnology & Biotechnological Equipment, 2021)
Ardisia gigantifolia is a medicinal plant; its herbal medicinal product has played important roles in the ways of life of people in China. However, commercial products of this herbal medicine are frequently adulterated with Rhododendron molle root and Clerodendrum cyrtophyllum stem. In fact, R. molle has hepatotoxic effects which could pose health issues to the end user. In this study, we applied DNA barcoding coupled with high resolution melting (Bar-HRM) to distinguish A. gigantifolia and adulterant products. Two DNA barcode loci (ITS2 and psbA-trnH) were chosen for Bar-HRM analysis. We found that ITS2 and psbA-trnH regions contain some inter-species variability, which showed enough discrimination capability for Bar-HRM analysis. We applied the Bar-HRM method to test the method, and found that some products labelled as “A. gigantifolia” collected from local markets in China were identified to contain C. cyrtophyllum. Our study demonstrated that DNA barcoding coupled with high resolution melting can be used as a routine test to guarantee the quality of A. gigantifolia herbal products.